John G. Nicolay papers - Nicolay, John G. (John George), 1832-1901.; Nicolay, Helen, 1866-1954.
Correspondence, research notes, notebooks, scrapbooks, and other papers relating chiefly to Nicolay's public career particularly his tenure as secretary to President Abraham Lincoln and to his numerous literary activities including his works on Lincoln. Also documents his service as U.S. consul, Paris, France, and U.S. Supreme Court marshal. Includes papers of his daughter, Helen Nicolay. Correspondents include John Bigelow, Anson Burlingame, Simon Cameron, Schuyler Colfax, Roscoe Conkling, William Dennison, John A. Dix, James Dixon, George Gilman Fogg, Horace Greeley, James Tracy Hale, James Harlan, O.M. Hatch, John Hay, Robert Todd Lincoln, Alexander K. McClure, Joseph Medill, Edwin D. Morgan, Charles H. Philbrick, Whitelaw Reid, Carl Schurz, Charles Sumner, Leonard Swett, Theodore Tilton, Horace White, A.C. Woolfolk, and Nicolay's wife, Therena Bates Nicolay.
Presidential secretary and biographer.
Collection material in English.
Finding aid and index available in the Library of Congress Manuscript Reading Room.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bigelow, John, -- 1817-1911 -- Correspondence; Burlingame, Anson, -- 1820-1870 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Dennison, William, -- 1815-1882 -- Correspondence; Dix, John A. -- 1798-1879 -- Correspondence; Dixon, James, -- 1814-1873 -- Correspondence; Fogg, George Gilman, -- 1813-1881 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Hale, James Tracy, -- 1810-1865 -- Correspondence; Harlan, James, -- 1820-1899 -- Correspondence; Hatch, O. M. -- 1814-1893 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; McClure, Alexander K. -- 1828-1909 -- Correspondence; Medill, Joseph, -- 1823-1899 -- Correspondence; Morgan, Edwin D. -- 1811-1883 -- Correspondence; Nicolay, Therena Bates, -- 1836-1885 -- Correspondence; Philbrick, Charles H -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Schurz, Carl, -- 1829-1906 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Swett, Leonard, -- 1825-1889 -- Correspondence; Tilton, Theodore, -- 1835-1907 -- Correspondence; White, Horace, -- 1834-1916 -- Correspondence; Woolfolk, A. C. -- -1880 -- Correspondence; United States. -- Supreme Court -- Officials and employees; Diplomatic and consular service, American -- France; France -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; Biographers; Secretaries, Presidential